Utilization of fluorescence spectroscopy as a novel approach to evaluate the oxidative stability in beef retail displayed. (September 2016) - Pouzo, L.B.; Zaritzky, N.E.; Pavan, E.; Rossetti, L.; Descalzo, A.M.
Abstract: Beef samples from grazing steers finished with different seed-supplemented diets were vacuum packaged for 3, 14 and 56 days (VC) and subsequently exposed to aerobic conditions (AE) for 0 and 5 days. Different fluorescent compounds of interest in the oxidation process were detected in meat, namely tryptophan residues, Schiff bases and porphyrins. Tryptophan intensity fluorescence increased with 14 days of VC; while Schiff bases intensity increased (P < 0.05) in beef samples stored under VC-56 and in all samples after AE-5 days. Porphyrins increased (P < 0.05) gradually with the extension of vacuum storage time, but were degraded in beef with long vacuum storage and 5 days of AE. Higher levels of porphyrins in beef under VC were correlated (P < 0.05) with lower redness and higher TBARS after AE-5. This study revealed the potential of fluorescence signals to detect oxidative changes in beef under different storage conditions using a fast and nondestructive method such as fluorescence spectroscopy. Highlights: Signals of Schiff bases increase with vacuum storage and aerobic exposure. Vacuum storage promoted porphyrin formation and oxidative damage in beef. Fluorescent compounds were related with lower redness and higher TBARS. Fluorescent signals could be used as a predictor of beef oxidative stability.